Color-Coded Stickers on Medical Record Document Folders at the Karanganyar Community Health Center - Salsabila, Mutiara; -, Harjanti; -, Noorlitasari (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Color coding aims to assign specific colors to Medical Record Folders. A problem encountered was the lack of color coding on Medical Record Folders, resulting in misplacement of medical records (misfiling). The research objective was to design color-coded stickers for Medical Record Folders. This applied qualitative research method involved two medical record officers, with the object being the Medical Record Folder. Data was collected through interviews and observation. Data validity was verified through triangulation of sources and methods. Data processing involved reduction, presentation, and drawing conclusions. The color-coded stickers measured 3 x 6 cm, were rectangular, folded, and placed on the medical record folders. The A3 mirror paper was divided into 75 stickers, each colored according to the number of regions: 12 within the region and 1 outside the region. The colors were purple, yellow, gray, dark green, orange, light blue, dark brown, magenta, light green, red, dark blue, black, pink, and gray. The content aspect was written using the third digit of each region code. Existing design suggestions to be followed up by creating color code stickers that will be attached to medical records so as to reduce the number of misfiling incidents.